Le emozioni nel dialogo cinematografico: implicito e tensioni drammatiche nei confronti verbali tra personaggi - Braga, Paolo (Rivista Italiana di Filosofia del Linguaggio, 2020)
Philosophy of language and semiotics have seldom studied cinematic dialogue. The topic has always gained limited attention also in research fields more directly interested in cinema, like film studies. Only recently, within the area of screenwriting studies, a few contributions have started to focus specifically on the importance of dialogue as a part of film as text. I will deal with this issue, specifically considering how dialogue creates subtext – i.e. layers of meaning implied by characters in their exchanges – and, through it, emotions. First, I will argue that dramatic subtext has two fundamental roots: the tension stemming from the character’s inner flaw, and the one stemming from his hidden agenda. On this basis, I will sketch a map of four main types of subtext. Finally, I will highlight which emotional pattern is typical of each kind of subtext, resulting from the interaction between character’s emotions and viewer’s emotions.